Sexual Dysfunction and its Treatment through Herbal Aphodisiacs - Semwal, Alok; Singh, Ramandeep; Azam, Mohammad (Journal of Pharmacy Practice and Community Medicine)
Dear Editor,The main essence of marriage in humans is proliferation and sexual fulfillment of male with a female in sexual intercourse. Apart from non living matter, all living things reproduce to make more organisms like themselves. Not only the male and female reproductive organs are essential for reproduction but also for a normal sexual intercourse the factors relating to the erection of the copulatory organ must function normally. The repeated inability of the male or female to perform this function, is termed as sexual dysfunction (SD).[1] Sexual dysfunction in male can be a result of physical or psychological disorder. Male sexual problems include decreased desire, orgasm disorder, erectile dysfunction, ejaculatory disorder and Detumescence failure.